Mindfulness and Coping Strategies among University students in light of the corona pandemic - Houria Chergui; Moulay Baghdad Djilali Belayachi (Social Empowerment Journal, 2021)
The aim of study is to identify the relationship between the mindfulness and the coping strategies among university students during CORONA Virus pandemic. The sample of the study is composed (55) students, )17(male and )38(female, spontaneously chosen from the faculty of human and social sciences of the university of MOSTAGANEM for the academic year 2020-2021. To realize the objects of the study we used the mindfulness module of Baer and al, 2004, and the CISS test. The results of the study showed a relationship between mindfulness and the coping strategies. The results also indicated a difference in the level of mindfulness between males and females, in favor of males.